Was Lockdown Racist? - Alex Broadbent; Pieter Streicher (Ergo, An Open Access Journal of Philosophy)
This paper argues that lockdown was racist, where “lockdown” refers to a historically situated kind of regulatory response to the Covid-19 pandemic imposing significant restrictions on leaving the home and on activities outside it. We articulate a notion of negligent racism which is objective and does not require intent, and show that lockdown satisfies its definition. The effects of lockdown on Africa significantly disadvantaged its inhabitants relative to the inhabitants of at least some other regions. We show how this suffices to establish the general proposition that lockdown was negligently racist (not merely “sometimes” or “someplace”), given our definitions. We defend our conclusion against two objections: that lockdown was a (moral) necessity (one version of which is the idea that it was a necessary precaution); and that race is explanatorily irrelevant, meaning that to whatever extent our argument is successful, it succeeds merely in showing that lockdown was anti-poor and not that it was racist. Nothing remains to gainsay the conclusion that lockdown was racist.